Quantitative and Qualitative Analysis of Sweat as a Biomarker - Jeyadaisy I.; Paarkavidevi C.; Sathish Kumar B.; Ammu G. (Contemporary Perspective on Science, Technology and Research Vol. 6, 2024)
Sweat glands (1.6–5 million) are distributed over the whole-body surface with an average density of 200 sweat glands per square centimeter. In the present medical scenario, several invasive methods are used to analyse the biomarkers in biofluids. Like, blood, urine, saliva and sweat, which are used for clinical analyses. Blood sampling is an invasive procedure, where patients require frequent analysis, are therefore at higher risk of infection. However, Its sample preparation, storage and plasma-protein removal is difficult. On the other hand, sweat analysis is very easy as compared with other biofluids, especially blood. The objective of the study is to analyse the transparent biofluid with low tonocity and slightly acidic nature with mean pH 6.3, which is more acidic than blood. Forehead sweat contains nitrogenous compounds like amino acids, lactic acid, electrolytes, urea and protein. A double beam uv-spectrophotometer2206 was used to determine amino acid, lactic acid and protein in sweat sample. Biomarkers were analysed qualitatively and quantitatively. To determine the abnormalities in human body by using analytical methods. With these methodologies, diseases like diabetes and cancers can be analysed cost-effectively.